2001
DOI: 10.2166/wst.2001.0713
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne epidemics in Finland in 1998-1999

Abstract: Fourteen waterborne epidemics occurred in Finland during 1998-1999. About 7,300 illness cases were registered in these outbreaks. All except one of the waterborne epidemics were associated with undisinfected groundwaters. An equal number of waterborne epidemics occurred in public and private water systems, but most cases of illness occurred in public water systems. The three largest epidemics comprised 6,700 illness cases. Insufficient purification treatment unable to remove Norwalk-like viruses caused the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 0 publications
0
64
0
Order By: Relevance
“…Health Climate change is also likely to affect water quality and quantity in Europe, and hence the risk of contamination of public and private water supplies (Miettinen et al, 2001;Hunter, 2003;Elpiner, 2004;Kovats and Tirado, 2006). Both extreme rainfall and droughts can increase the total microbial loads in freshwater and have implications for disease outbreaks and water-quality monitoring (Howe et al, 2002;Kistemann et al, 2002;Opopol et al 2003;Knight et al, 2004;Schijven and de Roda Husman, 2005).…”
Section: 433mentioning
confidence: 99%
“…Health Climate change is also likely to affect water quality and quantity in Europe, and hence the risk of contamination of public and private water supplies (Miettinen et al, 2001;Hunter, 2003;Elpiner, 2004;Kovats and Tirado, 2006). Both extreme rainfall and droughts can increase the total microbial loads in freshwater and have implications for disease outbreaks and water-quality monitoring (Howe et al, 2002;Kistemann et al, 2002;Opopol et al 2003;Knight et al, 2004;Schijven and de Roda Husman, 2005).…”
Section: 433mentioning
confidence: 99%
“…Climate change is also likely to affect water quality and quantity in Europe, and hence the risk of contamination of public and private water supplies (Miettinen et al, 2001;Hunter, 2003;Elpiner, 2004;Kovats and Tirado, 2006). Higher temperatures have implications for food safety, as transmission of salmonellosis is temperature sensitive Opopol and Nicolenco, 2004;van Pelt et al 2004).…”
Section: Human Healthmentioning
confidence: 99%
“…Various studies have shown that many disease outbreaks associated with water are preceded by heavy rainfall events [42][43][44][45][46][47][48]. An example of this phenomenon is with the cryptosporidiosis outbreak associated with borehole extracted groundwater, where heavy rainfall led to running water from, fecally polluted, cattle grazing fields leaking into the borehole water supply [44].…”
Section: Environmental Factors Affecting Disease Agentsmentioning
confidence: 99%